ANALYZING DYNAMICS AND STRUCTURE OF ISSUING INVESTMENT GOLD COINS - Nataliya V. Zolotova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
On the basis of economic analysis the author showed competitive struggle for the leading positions in the world rating of producers of investment gold coins. Interrelation between the volume of coins issue in conditions of economic crisis and investment, marketing, innovation decisions affecting their demand and supply was disclosed. The development of the situation on the market of investment gold coins was projected. The author points out to the constant increase in the role of investment in gold coins and its future prospects. She developed a methodological approach to the analysis of investment by countries, conducted their comparative analysis in respect to investment in Russia and showed the influence of the most important political and economic events in the world.